Depressive and Anxious Temperaments in Patients with Complex Regional Pain Syndrome Secondary to Tendon Injury. Issue 2 (June 2014) - Batmaz, Ibrahim; Dilek, Banu; Sariyildiz, Mustafa Akif; Erbatur, Serkan; Bez, Yasin; Yazmalar, Levent; Bozkurt, Mehtap; Çevik, Remzi
Abstract Objective: To determine the affective temperaments and somatoform amplification of the symptoms and its relation with the complex regional pain syndrome [CRPS] in patients who had tendon injuries of the forearm and hand. Methods: Sixty-seven patients [60 males, 7 females] with a forearm or hand tendon injury were enrolled in the present study. The patients were divided into two groups: CRPS and non-CRPS. The patients' pain levels within the last 48 hours were assessed using the visual analog scale [VAS]. The temperament of the patients was evaluated using the Temperament Evaluation of Memphis, Pisa, Paris and San Diego Auto questionnaire [TEMPS-A]. Their anxiety levels were evaluated with the help of the State-Trait Anxiety Inventory [STAI]. The depression assessment was performed using the Beck Depression Inventory [BDI]. The Somato sensory Amplification Scale [SSAS] was employed for the evaluation of the somatoform disorders. Results: The mean age of the patients was 26.21 ± 8.01 years [age range: 18 to 57 years]. Among the patients 24 [35.8%] had developed CRPS. When the patients with and without CRPS were compared in terms of their psychological scores, the STAI-II and BDI scores were observed to be significantly deteriorated in the CRPS group in comparison to the non-CRPS group [p < 0.05]. Among the TEMPS-A subtypes, anxious [16.7%] and depressive [41.7%] temperaments were more dominant in the CRPS group and the ratio was significantly more deteriorated than the non-CRPS group [p < 0.05]. No significant difference was observed between the groups regarding the SSAS scores [p > 0.05]. Conclusion: The present study is the first one evaluating the affective temperaments of CRPS patients with tendon injury, and the main findings point out that depressive and anxious temperaments are the most common dominant affective temperaments among our patients.